The Effect of Principal Transformational Leadership on the Performance of Islamic Education Teachers - Wafa, Moh Ali (Jurnal Ar Ro'is Mandalika (Armada), 2022)
The transformational leadership of school principals has a significant impact on the performance of Islamic education teachers. This article discusses the effect of transformational leadership of school principals on the performance of Islamic education teachers. The research method used is qualitative by conducting literature studies and library research. This study aims to explore the relationship between the transformational leadership style of school principals and the performance of Islamic education teachers. The results showed that the transformational leadership of school principals has a positive impact on the performance of Islamic education teachers, by inspiring, motivating, and empowering teachers to achieve Islamic education goals. An inclusive leadership approach, building good relationships, and providing strong support to teachers also play a role in improving their performance. However, challenges such as lack of leadership training for principals and instability of the school environment can affect the implementation of transformational leadership. Therefore, efforts are needed to improve the principal's understanding and transformational leadership skills as well as create a supportive school environment to improve the performance of Islamic education teachers